Anti-inflammatory effects of eugenol nanoemulsion as a topical delivery system. (2nd October 2016) - Esmaeili, Fariba; Rajabnejhad, Saeid; Partoazar, Ali Reza; Mehr, Shahram Ejtemaei; Faridi-Majidi, Reza; Sahebgharani, Mousa; Syedmoradi, Leila; Rajabnejhad, Mohammad Reza; Amani, Amir
Abstract: Eugenol is the main constituent of clove oil with anti-inflammatory properties. In this work, for the first time, O/W nanoemulsion of eugenol was designed for the evaluation of anti-inflammatory effects as a topical delivery system. Topical formulations containing 1%, 2% and 4% of eugenol as well as a nanoemulsion system containing 4% eugenol and 0.5% piroxicam were prepared. Further to physicochemical examinations, such as determination of particle size, polydispersity index, zeta potential and physical stability, anti-inflammatory activity was examined in carrageenan-induced paw edema in rats. The optimum formulation was found to contain 2% eugenol (oil phase), 14% Tween 20 (surfactant) and 14% isopropyl alcohol (co-surfactant) in water. Nanoemulsion with polydispersity index of 0.3 and median droplet diameter of 24.4 nm ( d 50 ) was obtained. Animal studies revealed that the nanoemulsions exhibited significantly improved anti-inflammatory activity after 1.5 h, compared with marketed piroxicam gel. Additionally, it was shown that increasing the concentration of eugenol did not show higher inhibition of inflammation. Also, the nanoemulsion having piroxicam showed less anti-inflammatory properties compared with the nanoemulsion without piroxicam.